101 silly summertime jokes - Calmenson, Stephanie; Orehek, Don (New York : Scholastic, 1989)
Over 140 jokes, including camp crackups, cool ghouls, seaside sillies, beach bound biggies, and more--Back cover.
5.5
5-8
490L
Keywords: Wit and humor, Juvenile; Jokes; Wit and humor; Jokes; Wit and humor